Aplasia cutis congenita on the scalp: case report and review of literature - Tiago Lima Castro; Carolina Garcia Pereira; Queila Esteves de Oliveira; Leandro Meirelles Nunes (Residência Pediátrica, 2023)
INTRODUCTION: Congenital Cutaneous Aplasia is a rare skin lesion, usually restricted to the scalp, characterized by a focal absence of cutaneous tissue, sometimes involving muscles, periosteum and dura mater. There are several etiologies described, such as poor neural tube closure, vascular anomalies, pressure necrosis in the localized embryo, among others. METHOD: We report the case of a newborn at the first physical examination with an annular vesicular lesion, in the occipital region, of 0.8 cm in greater diameter, with hyaline / bloody content and peripheral hyperemia. After a clinical diagnosis was made, we opted for conservative treatment with topical application of hydrogel until complete healing. The patient was then discharged from the hospital, with subsequent return and resolution of the lesion at 30 days of life. CONCLUSION: Congenital cutaneous aplasia is a rare disease, which can affect only the scalp, but can also present with the absence of part of the skullcap, which increases mortality due to the increased risk of complications such as liquor fistula, meningoencephalitis and bleeding.